An assessment of the survival impact of multimodal anesthesia/analgesia technique in adults undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy: a propensity score matched analysis. (1st January 2019) - Cata, Juan P.; Nguyen, Linh T.; Ifeanyi-Pillette, Ifeyinwa C.; Van Meter, Antoinette; Dangler, Lori A.; Feng, Lei; Owusu-Agyemang, Pascal
Abstract: Background: Studies suggest volatile anesthetics and opioids may enhance the malignant potential of cancer cells. The objective of this single institution retrospective study was to evaluate the survival impact of a multimodal opioid-sparing nonvolatile anesthetic technique (MA) in a group of patients who had undergone cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) for appendiceal carcinomatosis. Methods: Propensity score matching (PSM) and Cox proportional hazard models were used to compare the survivals of patients who received MA (MA group), to those who received volatile-opioid anesthesia (volatile-opioid group). Results: Of the 373 patients, 110 (29%) were in the MA group and 263 (71%) in the volatile-opioid group. The MA group was older (mean ± standard deviation (SD): 55 ± 11 versus 53 ± 10 years, p = .035) and had more patients with ASA scores 3 or 4 (90% versus 81%, p = .032), and those with high grade tumors (18% versus 12%, p = .009). Intraoperative opioid consumption was lower in the MA group (mean morphine equivalents ± SD: 13 ± 10 versus 194 ± 789, p < .0001). After PSM, 107 patients remained in each group. In the adjusted Cox proportional hazards model after PSM, MA was not associated with improved progression free survival (PFS) (HR 1.45, 95% CI [0.94–2.22], p = .093) or overall survival (OS) (HR 1.66, 95% CI [0.86–3.20], p = .128), when compared to volatile-opioid anesthesia. Conclusions: In this retrospective study, a multimodal opioid-sparing nonvolatile anesthetic approach was not associated with improved survival. Precis' statement: In this study of patients undergoing major cancer surgery, the use of multimodal anesthetic and analgesic agents, while avoiding volatile anesthetics and minimizing opioid use was not associated with improved survival.